👤


21. Aduceţi la forma cea mai simplă expresia:
c) (3m-2)(3m+2)+4;
e) 562 +(3 – 2b)(3+2b);
g) (0,8x+15)(0,8x –15)+0,36x?;
Va roog nu am timp​


Răspuns :

Răspuns:

[tex](3m + 2)(3m - 2) + 4 = {9m}^{2} + 6m - 6m - 4 + 4 = {9m}^{2} [/tex]

Tăiem (simplificam) +6m si-6m si - 4 cu +4 si este egal cu 9m la a doua

[tex]562 + (3 - 2b)(3 + 2b) = 562 + 3 + 6b - 6b - {4b}^{2} = 571 - {4b}^{2} [/tex]

Tăiem (simplificam) +6b si - 6b

[tex](0.8x + 15)(0.8x - 15) + 0.36x = {0.64x}^{2} - 12x + 12x - 225 + 0.36x = {0.64x}^{2} - 225 + 0.36x[/tex]